Efficient Two-Dimensional Perovskite Solar Cells Realized by Incorporation of Ti3C2Tx MXene as Nano-Dopants - Jin, Xin; Yang, Lin; Wang, Xiao-Feng (Nano-micro letters, 2021)
Highlights 2D Ti 3 C 2 T x MXene nanosheets with high electrical conductivity and mobility were employed as a nanosized additive to prepare 2D perovskite films. Doping of Ti 3 C 2 T x nanosheets can passivate the defects on the perovskite films surface and accelerate charge transfer process in vertical direction. Enhanced crystallinity and orientation of the perovskite films result in a significant increase in short-circuit current density and power conversion efficiency. Two-dimensional (2D) perovskites solar cells (PSCs) have attracted considerable attention owing to their excellent stability against humidity; however, some imperfectness of 2D perovskites, such as poor crystallinity, disordered orientation, and inferior charge transport still limit the power conversion efficiency (PCE) of 2D PSCs. In this work, 2D Ti 3 C 2 T x MXene nanosheets with high electrical conductivity and mobility were employed as a nanosized additive to prepare 2D Ruddlesden–Popper perovskite films. The PCE of solar cells was increased from 13.69 (without additive) to 15.71% after incorporating the Ti 3 C 2 T x nanosheets with an optimized concentration. This improved performance is attributed to the enhanced crystallinity, orientation, and passivated trap states in the 3D phase that result in accelerated charge transfer process in vertical direction. More importantly, the unencapsulated cells exhibited excellent stability under ambient conditions with 55 ± 5% relative humidity.